The Semiotic Essence of Grammatical Construction - A. S. Druzhinin (Vestnik MGIMO-Universiteta)
The article explores the peculiarities of semiosis of grammatical construction from the perspective of modern studies into cognitive linguistics. Setting out the bio-socio-cultural sign theory fundamental for this research, the author defines a grammatical construction as a complex representation of mental images and offers a model of cognitive processes connected with its functioning in language and discourse as illustrated by the example of a Subjunctive Mood form.